Novel Genetic Dysregulations and Oxidative Damage in Fusarium graminearum Induced by Plant Defense Eliciting Psychrophilic Bacillus atrophaeus TS1 - Muhammad Zubair (MDPI AG, 2021)
This study elaborates inter-kingdom signaling mechanisms, presenting a sustainable and eco-friendly approach to combat biotic as well as abiotic stress in wheat. Fusarium graminearum is a devastating pathogen causing head and seedling blight in wheat, leading to huge yield and economic losses. Psychrophilic Bacillus atrophaeus strain TS1 was found as a potential biocontrol agent for suppression of F. graminearum under low temperature by carrying out extensive biochemical and molecular studies in comparison with a temperate biocontrol model strain Bacillus amyloliquefaciens FZB42 at 15 and 25 °C. TS1 was able to produce hydrolytic extracellular enzymes as well as antimicrobial lipopeptides, i.e., surfactin, bacillomycin, and fengycin, efficiently at low temperatures. The Bacillus strain-induced oxidative cellular damage, ultrastructural deformities, and novel genetic dysregulations in the fungal pathogen as the bacterial treatment at low temperature were able to downregulate the expression of newly predicted novel fungal genes potentially belonging to necrosis inducing protein families (fgHCE and fgNPP1). The wheat pot experiments conducted at 15 and 25 °C revealed the potential of TS1 to elicit sudden induction of plant defense, namely, H2O2 and callose enhanced activity of plant defense-related enzymes and induced over-expression of defense-related genes which accumulatively lead to the suppression of F. graminearum and decreased diseased leaf area.